2010
DOI: 10.1007/s10750-010-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing macroinvertebrate assemblages in artificial subtropical ponds of Taiwan

Abstract: Macroinvertebrate assemblages and its association with environmental factors at the 11 artificial subtropical ponds of Taiwan were examined using the multivariate analysis software STATICO. The aims of the study were to determine whether spatial and seasonal variation of macroinvertebrate assemblages changed seasonally, to examine which environmental factors determined the spatial and temporal structure of maroinvertebrate assemblages, and to compare between-pond variations in the taxon composition of macroinv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…On the other hand, these small aquatic systems are rich and diverse habitats and play a key role in safeguarding aquatic biodiversity Shieh, and Chi 2010). These systems are considered to support a high richness of organisms, particularly macroinvertebrates (Oertli et al 2002;Williams et al 2004), both on a local and regional scale (Toro et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these small aquatic systems are rich and diverse habitats and play a key role in safeguarding aquatic biodiversity Shieh, and Chi 2010). These systems are considered to support a high richness of organisms, particularly macroinvertebrates (Oertli et al 2002;Williams et al 2004), both on a local and regional scale (Toro et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pond size has been reported to be a key influence on macroinvertebrate composition within ponds, (Brönmark 1985;Nilsson and Svensson, 1995;Biggs et al, 2005;Stenert and Maltchik, 2007;Ruggiero et al, 2008;Shieh and Chi, 2010) as a greater surface water area can allow larger populations to develop and reduce the chance of extinction (Shieh and Chi, 2010). However, some studies found that pond size has relatively little influence on community composition (Scheffer et al, 2006;Nakanishi et al, 2014).…”
Section: Local (Physicochemical/biological) and Spatial (Connectivitymentioning
confidence: 99%
“…Signal crayfish (Pacifastacus leniusculus) deleteriously impacted snail abundance. Shieh & Chi, 2010Kett & Kirk, 1994Krull, 1970Nyström et al, 2001 dries and re-colonize quickly as the pond fills to exploit the resources (Vanschoenwinkel et al, 2009). Macroinvertebrate richness and abundance increased in accordance with increasing hydroperiod length in ephemeral ponds in New Hampshire, USA (Tarr et al, 2005).…”
Section: Local (Physicochemical/biological) and Spatial (Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…As an important habitat for aquatic macroinvertebrates, the pond ecosystem has been paid much attention to its different components, the macroinvertebrate assemblages were often a matter of atenton [1,41,42]. ponds in southern England [29].…”
Section: Macrobenthos Assemblage Structure and Composition In Three Mmentioning
confidence: 99%